PRIMARY TEACHERS KNOWLEDGE ABOUT PSYCHOMOTOR DISTURBANCES OCCURING IN CHILDREN - Agata Nowak; Anna Romanowska-Tolloczko; Monika Knysak (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Objective: An attempt to determine the level of knowledge of teachers in the symptoms, diagnosis and treatment of psychomotor disorders of schoolchildren. Materials and methods: 174 teachers of physical education and integrated education in primary schools were tested. The study used questionnaire technique. Results: As the most common disorders in the population of school-age children surveyed teachers list ADHD (30%) and dyslexia (30%). Only 34% of respondents correctly determined epidemiology of psychomotor disorders and listed their symptoms. Over 80% of respondents claimed that they had never worked with children exhibiting psychomotor disorders. The majority of respondents (98%) did not participate in training on working with children with developmental disabilities. Results: The state of knowledge of psychomotor disorders of the surveyed teachers is low. Teachers have difficulty not only in defining the epidemiology of various disorders but also in correct definition of symptoms full spectrum.